Afterward: Preparing for uncertainties. Issue 1 (May 2016) - KULSTAD GONZÁLEZ, TESS; FAAS, A. J.
Abstract : As the frequency and intensity of disasters increase around the world in the context of a changing climate, the likelihood that disasters will impact anthropological field sites increases. Therefore, disasters will increasingly become an expected component of anthropological work. In this article, the authors discuss the ways in which risk, hazards, and disasters will change anthropological research, practices, and methodologies as a whole.